Temperature- and pH-sensitive core-shell nanoparticles self-assembled from poly(N-isopropylacrylamide-co-acrylic acid-co-cholesteryl acrylate) for intracellular delivery of anticancer drugs - Wei, J.-S. (2014)
Frontiers in Bioscience